Comparison of doses to the rectum derived from treatment planning system with in-vivo dose values in vaginal vault brachytherapy using cylinder applicators - Oyekunle, Emmanuel Oyeyemi; Obed, Rachel Ibhade; Akinlade, Bidemi Idayat; Ntekim, Atara (Journal of Contemporary Brachytherapy, 2015)
Purpose : In-vivo measurements to determine doses to organs-at-risk can be an essential part of brachytherapy quality assurance (QA). This study compares calculated doses to the rectum with measured dose values as a means of QA in vaginal vault brachytherapy using cylinder applicators. Material and methods: At the Department of Radiotherapy, University College Hospital (UCH), Ibadan, Nigeria, intracavitary brachytherapy (ICBT) was delivered by a GyneSource high-dose-rate (HDR) unit with 60Co. Standard 2D treatment plans were created with HDR basic 2.6 software for prescription doses 5-7 Gy at points 5 mm away from the posterior surface of vaginal cylinder applicators (20, 25, and 30 mm diameters). The LiF:Mg, Ti thermoluminescent dosimeter rods (1 x 6 mm) were irradiated to a dose of 7 Gy on Theratron 60Co machine for calibration purpose prior to clinical use. Measurements in each of 34 insertions involving fourteen patients were performed with 5 TLD-100 rods placed along a re-usable rectal marker positioned in the rectum. The dosimeters were read in Harshaw 3500 TLD reader and compared with doses derived from the treatment planning system (TPS) at 1 cm away from the dose prescription points. Results : The mean calculated and measured doses ranged from 2.1-3.8 Gy and 1.2-5.6 Gy with averages of 3.0 ± 0.5 Gy and 3.1 ± 1.1 Gy, respectively, for treatment lengths 2-8 cm along the cylinder-applicators. The mean values correspond to 48.9% and 50.8% of the prescribed doses, respectively. The deviations of the mean in-vivo doses from the TPS values ranged from –1.9 to 2.1 Gy with a p-value of 0.427. Conclusions : This study was part of efforts to verify rectal dose obtained from the TPS during vaginal vault brachytherapy. There was no significant difference in the dose to the rectum from the two methods of measurements.